1983
DOI: 10.1159/000233309
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against Polyethylene Glycol Produced in Animals by Immunization with Monomethoxy Polyethylene Glycol Modified Proteins

Abstract: Antibodies to polyethylene glycol (PEG) were raised in rabbits by immunization with monomethoxy polyethylene glycol modified ovalbumin (OA), bovine superoxide dismutase (SOD), and ragweed pollen extract (Rag), given in Freund’s complete adjuvant (FCA). Immunogenicity depended on the nature of the protein and the degree of modification. With modified OA, in the presence of FCA, the majority of animals showed an anti-PEG response. With modified SOD and Rag only a small proportion of animals responded. In the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
183
2
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(201 citation statements)
references
References 15 publications
(17 reference statements)
8
183
2
4
Order By: Relevance
“…Richter and Akerblom 27) proposed in an earlier study that the antigenic determinant of PEG may be a sequence of 6-7 -CH 2 CH 2 O-units. Roffler and co-workers 35,36) demonstrated that the monoclonal anti-PEG IgM generated by antibody-PEG-modified βG recognizes the repeating sequence (16 -CH 2 CH 2 O-units) of PEG.…”
Section: Discussionmentioning
confidence: 99%
“…Richter and Akerblom 27) proposed in an earlier study that the antigenic determinant of PEG may be a sequence of 6-7 -CH 2 CH 2 O-units. Roffler and co-workers 35,36) demonstrated that the monoclonal anti-PEG IgM generated by antibody-PEG-modified βG recognizes the repeating sequence (16 -CH 2 CH 2 O-units) of PEG.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Richer and Akerblom 15) demonstrated that subcutaneous administration of free PEG to mice elicits a weak and transitory immune response. In addition, they showed that a stronger anti-PEG immune response was found with PEGylated proteins, particularly ovalbumin (oVA).…”
Section: Anti-peg Immunoglobulin M (Igm) Response To Pegylated Proteinsmentioning
confidence: 99%
“…Thus far, PRCA caused by pegylated interferon has previously been reported [16][17][18]. PEG is generally considered non-immunogenic by itself; however, a strong anti-PEG immune response was reported for some pegylated proteins, particularly ovalbumin [19], and mice exposed to adenovirus modified with a high molecular weight PEG showed a strong immune response compared to those exposed to the unmodified adenovirus [20]. Therefore, in our case, the induction of autoimmunity to the pegylated glycoprotein is the most probable pathogenesis of PRCA development including the inhibition of erythropoiesis, although we cannot exclude other possibilities because PRCA itself is an incidental complication in HD patients [11].…”
Section: Discussionmentioning
confidence: 99%